The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.5902/19805098890
|View full text |Cite
|
Sign up to set email alerts
|

El análisis bayesiano y la precisión de los valores de la heredabilidad en especies perennes

Abstract: RESUMENLos objetivos del presente trabajo fueron evaluar la precisión del valor estimado de la heredabilidad determinada por medio de la desviación estándar, considerando un enfoque Bayesiano, y comparar tal estimativa con el procedimiento clásico. Se utilizaron datos de un ensayo de progenie con 39 familias de Eucalyptus cladocalyx. La variable dependiente usada fue el diámetro basal del fuste medido a los seis años de edad. El método Bayesiano fue implementado por medio del algoritmo de Cadenas Independiente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Mora et al (2009) used the Bayesian approach to predict the heritability values of forest species, and concluded that this method made it possible to obtain low standard deviation values associated with heritability, which makes it an important tool for genetic breeding. Silva et al (2013) used the Bayesian approach to select sugarcane families (Saccharum officinarum L.), and found that the informative a priori not only influenced the genetic effects, but it also influenced variance and heritability.…”
Section: Introductionmentioning
confidence: 99%
“…Mora et al (2009) used the Bayesian approach to predict the heritability values of forest species, and concluded that this method made it possible to obtain low standard deviation values associated with heritability, which makes it an important tool for genetic breeding. Silva et al (2013) used the Bayesian approach to select sugarcane families (Saccharum officinarum L.), and found that the informative a priori not only influenced the genetic effects, but it also influenced variance and heritability.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2009) showed that calculating genotypic probabilities increased the precision of additive effect estimates and decreased the error estimate associated with the Bayesian model. Mora et al (2009) used Bayesian analysis to predict the inheritability values for forest species and concluded that the Bayesian method makes it possible to obtain low standard deviation values associated with inheritability, which makes it an important tool for the genetic assessment and inference of perennial species. Balestre et al (2012) conducted a Bayesian survey of multiple corn ( Zea mays L.) characteristics, in which they highlighted the importance of pleiotropic effects in the study of the inheritance of quantitative characteristics.…”
mentioning
confidence: 99%